PCC pilot plant studies with aqueous potassium glycinate. (November 2015) - Rabensteiner, Markus; Kinger, Gerald; Koller, Martin; Hochenauer, Christoph
Highlights: Realistic study by power plant flue gas and industrial dimensions of pilot plant. The energy demand increases significantly when using KGly in comparison to MEA. The required solvent stream is very high. Excessive pressure drop in the desorber can lead to plant failure. High ammonia emissions despite of ionic structure of amino acid salts. Abstract: The present research work discusses the suitability of aqueous potassium glycinate (KGly) in a PCC-pilot plant. Reference is made to measurement results with aqueous sodium glycinate (NaGly). The use of real power plant flue gas and the well-conceived dimensions of the test facility enable industry-related conditions for full-scale applications. Although 40 wt% KGly has faster kinetics in unloaded state, no enhancements in plant operation could be achieved in comparison to 40 wt% NaGly. Just like with NaGly, the difficult feasibility of KGly regeneration leads to slow CO2 absorption rates, resulting in a huge energy demand > 5.5   GJ / t CO 2 . A far lower energy demand of 3.68   GJ / t CO 2 was measured for 30 wt% MEA. The required solvent flow rate for reaching the optimal operating point is high (L/G-ratio = 9 l/m 3 ). The pilot plant was operated with a massive reduced flue gas flow (40% of the dimensioning) in order to prevent instable operation and to reach the desired CO2 separation efficiency of 90%. During a prolonged shutdown, excessive carbonate was formed in the desorber column, resulting in a further reduction of the flue gas flow rate. Measurements of the ammonia content of the treated flue gas exhibit that the solvent degrades enormously.